Construction and validation of an instrument to assess the reading comprehension of students from the third to the fifth grades of elementary school - Vera Lúcia Orlandi Cunha; Simone Aparecida Capellini (CoDAS)
Purpose: In this study, we aimed at building and validating an instrument to assess reading comprehension, with the purpose of characterizing the reading profile and detecting comprehension difficulties among students from the third to the fifth grades of elementary school. Methods: Participants were 378 students, divided into three groups. Their comprehension of micro- and macrostructural literal and inferential propositions that composed two expository texts and two narrative texts were assessed by means of multiple-choice questions. Results: The data analyzed statistically yielded Cronbach's alpha values showing internal consistency in the four texts applied to the three groups. Conclusion: It was possible to verify that the students had fewer errors as the school years progressed and that each type of text posed a particular difficulty to the students.